2013
DOI: 10.1371/journal.pone.0056380
|View full text |Cite
|
Sign up to set email alerts
|

CD133 Expression and the Prognosis of Colorectal Cancer: A Systematic Review and Meta-Analysis

Abstract: ObjectiveCD133 has recently been reported as a marker of cancer stem-like cells in colorectal cancer (CRC). However, its predictive value in CRC still remains controversial. In this study, we aimed to evaluate the association between the expression of CD133 and clinicopathological features and the outcome of CRC patients by performing a meta-analysis.MethodsA comprehensive literature search for relevant studies published up to December 2012 was performed using PubMed, MEDLINE and ISI Web of Science. Only artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
105
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 57 publications
10
105
0
3
Order By: Relevance
“…Other contradicting results were reported by Yamamoto et al who found CD133 expression in liver metastases to be associated with a better OS after hepatectomy (16) and Kishikawa et al who reported both a better OS and DFS (18). Even though discrepancies exist between the results of the few available studies, the current findings are in accordance with results of the considerably larger available material on the prognostic value of CD133 expression in primary CRC, where a meta-analysis associated this with a worse prognosis as well (15). Since there was no significant discordance between CD-133 expression in the primary colon cancer and the liver metastases in the present material, these findings are most likely associated.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Other contradicting results were reported by Yamamoto et al who found CD133 expression in liver metastases to be associated with a better OS after hepatectomy (16) and Kishikawa et al who reported both a better OS and DFS (18). Even though discrepancies exist between the results of the few available studies, the current findings are in accordance with results of the considerably larger available material on the prognostic value of CD133 expression in primary CRC, where a meta-analysis associated this with a worse prognosis as well (15). Since there was no significant discordance between CD-133 expression in the primary colon cancer and the liver metastases in the present material, these findings are most likely associated.…”
Section: Discussionsupporting
confidence: 86%
“…More knowledge exists on these markers' expression in primary colon cancer and outcome after colon cancer treatment, with CD133 being claimed to be associated with both a worsened OS and DFS after colon cancer treatment (15). CD44 expression is found to predict a worsened OS (13), as is CD24 (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ese large discrepancies have been attributed mainly to methodological variations and di erent scoring systems [18,46,47]. It seems that only membranous CD133 overexpression correlates with patient survival times, recurrence-free survival times and chemoresistance [21,48]. However, it was speculated that the shi of CD133 from cytoplasmic to a membranous localization underlies the transition of epithelial cells towards a more invasive phenotype [48].…”
Section: Cd133 and Cd166 Expression Patternsmentioning
confidence: 99%
“…Повышенные ее уровни в периферической крови предсказывали рецидив колоректального рака независимо от стадии опухоли и уровней раково-эмбрионального анти-гена и были ассоциированы с костными метастазами в раз-личных солидных опухолях [16]. В ряде систематических обзоров и метаанализов показана меньшая выживаемость пациентов с раком желудка [53], яичников [54], немелко-клеточным раком легкого [55], колоректальным раком [56] при высокой экспрессии СD133 в опухоли.…”
unclassified